Vom Regen in die Traufe? : Unbesetzte Ausbildungsstellen als künftige Herausforderung des Ausbildungsstellenmarktes - Troltsch, Klaus [Verfasser]; Gerhards, Christian [Verfasser]; Mohr, Sabine [Verfasser] (Bertelsmann, 2012)
Jeder dritte Ausbildungsbetrieb in Deutschland hat inzwischen große Schwierigkeiten bei der Besetzung seiner Ausbildungsstellen. Im Beitrag wird auf der Grundlage einer aktuellen Betriebsbefragung des BIBB beschrieben, welche Betriebe in besonderer Weise davon betroffen sind und von welchen betriebsinternen und -externen Faktoren dies in erster Linie abhängt. Trotz dieser Probleme bei der Stellenbesetzung will sich die Mehrheit der Betriebe auch künftig an der Ausbildung beteiligen. (BIBB-Doku)

"Although demographic change and its attendant consequences for the dual training system are not being revealed to the massive extent predicted by many, its effects on the training places market are already clearly discernible. Whereas for many young people the search for vocational education and training places was long characterised by unsuccessful application letters, by waiting loops extending over periods of several years and by career choice compromises, their initial opportunities are now improving on a step-by-step basis albeit without any indication that conditions on the training places market could yet be described as satisfactory. Demographic upheaval means that increasing numbers of companies are unable to fill the training places they have on offer and are being left empty-handed as they seek to recruit young skilled workers for their own company-based training." (Authors' abstract, BIBB-Doku)
Out of the frying pan and into the fire? : Vacant training places a future challenge faced by the training places market
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; Ausbildungsstellenmarkt; Ausbildungsstellenbilanz; Ausbildungsverhalten; Personalgewinnung